1975
DOI: 10.1136/bmj.2.5966.315
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma of the oesophagus with "swallow syncope".

Abstract: BRITISH MEDICAL JOURNAL10 MAY 1975 315 energy shocks were successful then. The initial shock was unsuccessful in 7%O (two out of 28) of patients with primary fibrillation, but a second shock of identical energy was successful in both patients. The success of the second shock when the initial one has failed29 may be related to the decreased impedance with successive shocks.30 Apart from allowing smaller and lighter defibrillators these lower energy shocks cause less myocardial damage.Our findings indicate the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…Reflex-mediated vasomotor inhibitory syndrome is one of the etiological categories of syncope, and swallow syncope, included in this category, is a relatively rare syndrome[1]. To our knowledge, since Spens [2 ]described a possible case of swallow syncope in 1793, about 60 cases have been reported in the English literature (table 1) [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57]. Most patients were adults, of varying ages, but some cases of young children have also been reported [16, 29, 31, 33], and the possibility of hereditary factors has been suggested [29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflex-mediated vasomotor inhibitory syndrome is one of the etiological categories of syncope, and swallow syncope, included in this category, is a relatively rare syndrome[1]. To our knowledge, since Spens [2 ]described a possible case of swallow syncope in 1793, about 60 cases have been reported in the English literature (table 1) [2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57]. Most patients were adults, of varying ages, but some cases of young children have also been reported [16, 29, 31, 33], and the possibility of hereditary factors has been suggested [29].…”
Section: Discussionmentioning
confidence: 99%
“…Swallow syncope occurred in the presence of underlying esophageal diseases (i.e. esophageal spasm [7, 10, 19, 25, 30], esophageal stricture [15, 20], achalasia [11, 43, 49], esophageal diverticulum [6, 8, 9], hiatus hernia [17, 19, 25, 28, 54, 56] and esophageal cancer [21, 22, 45]), and heart disease (myocardial infarction [9, 13, 18, 26, 18], rheumatic carditis [2], and digoxin use [8, 17, 30]). Some cases were reported to be associated with thoracic surgery [16, 26, 35, 51], advanced lung cancer [18, 42] and transient hypoxia [51].…”
Section: Discussionmentioning
confidence: 99%
“…Paroxysmal vagally dependent AV block resulting in syncope, but without associated electrocardiogram abnormality, is not a well recognized phenomenon. Sporadic cases of complete heart block related to certain vagotonic reflexes, such as coughing (Hart et al, 1982) and swallowing (Sapru et al, 1971;Tomlinson and Fox, 1975;Wik and Hillestad, 1975) have been reported. Two patients with recurrent vagally mediated complete AV block without any precipitating event were described by Strasberg et al, (198 1).…”
Section: Introductionmentioning
confidence: 99%
“…The leadtime before diagnosis ranges from days to decades [3,4]. Dysphagia or odynophagia is present only in a subgroup of patients with swallow syncope [5][6][7][8][9][10][11][12], and it has been reported with ingesting solid food [10,13,, hot or cold liquids [11,[16][17][18], and carbonated beverages [19,[20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%